Four New Picrotoxane-Type Sesquiterpenes From Dendrobium nobile Lindl - Wang, Pei; Chen, Xin; Wang, Hao; Huang, Shengzhuo; Cai, Caihong; Yuan, Jingzhe; Zhu, Guoliang; Xu, Xinglian; Mei, Wenli; Dai, Haofu (Frontiers in Chemistry, 2019)
Four picrotoxane-type sesquiterpenes, dendroterpene A–D (1–4), together with four known compounds (5–8), were isolated from the stems of Dendrobium nobile Lindl. Their structures were elucidated by spectroscopic analysis, X-ray diffraction analysis, analysis of the ECD data according to the Klyne's lactone sector rule, and quantum ECD calculation. Compounds 1 and 2 are two new picrotoxane-type sesquiterpenes with a new carbon skeleton containing a formamide group, which may be derived from the previously reported dendrobiumane B skeleton by the C(9)-C(11) carbon bond cleavage. Compounds 3, 5, 6, and 8 exhibited inhibitory activity against α-glycosidase. Compounds 5 and 6 were cytotoxic against SGC-7901, K562, A549, BEL-7402, and Hela cell lines.